Important but challenging: Chinese in-service EFL teachers’ research attitudes in a graduate program - Chen, Lei; Liu, Quanguo (Frontiers in Psychology, 2023)
In recent decades, the practice of involving teachers in research in degree programs is becoming popular. Yet, little is known about the impact of research experiences on teachers' behavior: whether research experiences change their teaching practices and lead to further research efforts in future careers, especially in the unique social, cultural, and educational culture of China. Thus, this study examines Chinese IETs' (in-service EFL teachers') research attitudes in a graduate program with a reasoned action approach. We used an embedded mixed methods research design to investigate a cohort of 197 IETs who completed the Research Attitudes in Vocational Education Questionnaire (RAVE-Q). The quantitative data validates the survey and shows that, in general, the IETs hold positive attitudes toward research. Next, semi-structured interviews investigating IETs and their advisors' perceptions of teacher research were conducted. The qualitative data shows a variety of research experiences among the IETs. Specifically, this study highlighted some interviewed IETs who had the desire to be reflective about their teaching and to apply research in their practices, nevertheless, the educational contexts made such efforts impossible. Thus, this study questioned the previous assumptions that positive research attitudes lead to corresponding research behaviors. This study offers implications for EFL graduate programs seeking to improve IETs' research attitudes both within and outside China.